Klebsiella pneumoniae causing mass mortality in juvenile Nile tilapia in Brazil: Isolation, characterization, pathogenicity and phylogenetic relationship with other environmental and pathogenic strains from livestock and human sources - Vaneci-Silva, Daiane [UNESP]; Assane, Inácio Mateus [UNESP]; de Oliveira Alves, Lindomar [UNESP]; Gomes, Fernando Cardoso [UNESP]; Moro, Evandro Bilha [UNESP]; Kotzent, Suzana [UNESP]; Pitondo-Silva, André; Pilarski, Fabiana [UNESP] (Elsevier, 2022)
Klebsiella pneumoniae is a critical-priority human pathogen, considered a key trafficker of drug resistance genes from environmental to clinically important bacteria. Although current evidence suggests its potential role as aquatic pathogen, there are few reports of infections in cultured fish, and its pathogenicity to Nile tilapia remains unknown. Here we report the mass mortality in cultured Nile tilapia caused by a natural infection of K. pneumoniae, along with the bacteria isolation, phenotype, pathogenesis in Nile tilapia, and phylogenetic relationships with strains isolated from environmental, livestock, and human samples from different locations. High morbidity and mass mortality (~90 thousand fish within 4 days) of juvenile Nile tilapia (32 ± 6.0 g) occurred in July 2018 in a commercial fish farm located in Brazil. The main clinical signs during the outbreak included lethargy, anorexia, subcutaneous haemorrhages, urogenital bleeding, and ascites. The bacteria (n = 7) were isolated and identified as K. pneumoniae by morphological evaluation, biochemical tests, nucleotide sequencing and phylogenetic analysis of a partial sequence of the highly conserved 16S rRNA gene. All clinical isolates were catalase-positive, and the hypermucoviscous phenotype associated with hypervirulent K. pneumoniae was not detected. The pathogenicity for Nile tilapia and phylogenetic relationships with other K. pneumoniae strains were determined by experimental infection and phylogenetic reconstruction by maximum likelihood and Bayesian inference methods, respectively. All clinical isolates were included in the clade of K. pneumoniae, and most of them were differentiated from both environmental and pathogenic strains from different locations, including Brazil. Experimentally infected Nile tilapia exhibited similar clinical signs and severe histological changes in the liver, spleen, intestine, kidney, and gills as fish that were naturally infected, fulfilling Koch's postulates and demonstrating the virulence of the recovered strain. The LD10, 50, 90, and 99 were established in 2.1 × 103, 1.2 × 107, 1 × 1010, and 8.7 × 1013 colony-forming units (CFU)/mL, respectively. This is the first description of K. pneumoniae natural infection in Nile tilapia along with its pathogenesis, denoting a hidden risk for both animal and human health.
Keywords: Bacterial infection; Fish-borne zoonoses; Klebsiella pneumoniae; One Health; Oreochromis niloticus; Pathogenesis